2009
DOI: 10.1124/dmd.108.025981
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolism of14C-Labeled Apixaban in Mice, Rats, Rabbits, Dogs, and Humans

Abstract: ABSTRACT:The metabolism and disposition of [ 14 C]apixaban, a potent, reversible, and direct inhibitor of coagulation factor Xa, were investigated in mice, rats, rabbits, dogs, and humans after a single oral administration and in incubations with hepatocytes. In plasma, the parent compound was the major circulating component in mice,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 30 publications
2
78
0
3
Order By: Relevance
“…Apixaban was metabolized by numerous pathways and enzymes, primarily CYP3A4/5, with relatively minor contributions by CYP1A2, 2J2, 2C8, 2C9, and 2C19. This multiple-pathway metabolism of apixaban, in combination with the contribution of renal and biliary clearance as well as intestinal secretion to elimination (urinary, biliary, or intestinal clearance was more important than metabolic clearance) Zhang et al, 2009), indicates that alternative elimination routes are available, should the primary metabolic enzymes be inhibited. Therefore, although apixaban may be the victim of drug-drug interactions with drugs that modulate P450 enzymes, such interactions are not likely to be of any significant magnitude.…”
Section: Metabolic Drug-drug Interaction Potential Of Apixabanmentioning
confidence: 99%
“…Apixaban was metabolized by numerous pathways and enzymes, primarily CYP3A4/5, with relatively minor contributions by CYP1A2, 2J2, 2C8, 2C9, and 2C19. This multiple-pathway metabolism of apixaban, in combination with the contribution of renal and biliary clearance as well as intestinal secretion to elimination (urinary, biliary, or intestinal clearance was more important than metabolic clearance) Zhang et al, 2009), indicates that alternative elimination routes are available, should the primary metabolic enzymes be inhibited. Therefore, although apixaban may be the victim of drug-drug interactions with drugs that modulate P450 enzymes, such interactions are not likely to be of any significant magnitude.…”
Section: Metabolic Drug-drug Interaction Potential Of Apixabanmentioning
confidence: 99%
“…Metabolites in plasma, bile, and urine and fecal samples were profiled as described previously (Raghavan et al, 2009;Wang et al, 2011;Zhang et al, 2009a). Pooled plasma, urine, bile, or fecal homogenate samples were prepared by aliquoting appropriate volumes or weights of samples from each time interval.…”
Section: Materials Apixaban and [mentioning
confidence: 99%
“…Greater than 50% of radioactive dose was recovered in feces as the parent from rats, dogs, and humans following oral administration of [ 14 C]apixaban. Plasma radioactivity profiling has shown that apixaban represents .90% of all circulating drug-related components in rats and dogs and 75% in humans (Raghavan et al, 2009;Wang et al, 2011;Zhang et al, 2009a). Apixaban is metabolically stable in incubations with liver microsomes and hepatocytes and has a relatively low clearance with total plasma clearance of ,5% hepatic blood flow in rats, dogs, and humans Wong et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vartojant du kartus per parą, optimalus įsotinimas pasiekiamas per 3 paras [20]. Vaisto eliminacija vyksta per inkstus ir virškinimo traktą [21].…”
Section: Tyrimo Objektas Ir Metodasunclassified